Eye-tracking for disabled people - Alwani, Heetesh (2018)
The aim of this project is to design a high confidence mobility device that can be used by sufferers of amyotrophic lateral sclerosis (ALS) to move around independently. On average, 15 people are newly diagnosed with ALS every day [1] and eventually, they lose their ability to walk and are confined to wheelchairs. Worse still, they are unable to control their own wheelchair due to severe muscle weakness and hence need caregivers to move them around. However, they retain control of their eyes which can be used to interact with the environment around them. The objective of this project is to record eye gaze using modern eye-tracking technology to move a motorized wheelchair. In order to achieve this objective, steps were first taken to mimic joystick control using an Arduino Uno, followed by controlling the wheelchair with a Graphical User Interface that accepted mouse inputs, and finally integrating the system to accept inputs from an eye tracking device. At each stage of the project, the behaviour of the intended system was modelled, before a solution that fit the model was designed. The designed solution was then tested to determine if its behaviour was consistent with the model. Wheelchair control using an eye-tracker has been achieved in this project and is suitable for user testing. Nonetheless, improvements to the designed solution can still be made and recommendations on how to do so have been made in this report.